Improving Islamic Education Student Learning Outcomes Through the Video Method at SD Negeri 26 Kunangan Parit Rantang - Firnando, Rio (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using the video method. This research is classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research were elementary school students. This research data was obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with indicators of research success. The research results show that video media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of pre-cycle 40.49%, first cycle 54.77% and in the second cycle it increased to 85.22%. Thus, the use of videos can be used as an alternative to improve student learning outcomes in Islamic religious education learning.